Effects of Short Sprint Interval Training and Long Sprint Interval Training on Alactic and Lactic Anaerobic Capacities - S Syahruddin; Muhammad Syahrul Saleh; Muhammad Sahib Saleh; I Irmawati (Universitas Pendidikan Indonesia, 2022)
This research the aims tis to examine the influence of short sprint interval training (SPI) and long sprint interval training (LPI) on anaerobic capacity of Alactase (AA) and Lactase (LA). The subjects were 29 Junior Secondary students Makassar randomly selected from 50 students. They were divided into two groups based on the results of the initial test matching anaerobic capabilities Alactase. The first group was given a short sprint interval training (SPI) and group II were given a long sprint interval training (LPI). A Wingate test was used to measure the response variable. The parameters of the visits are the capacity of Alactase (AA) and capacity Lactase (LA). Results of the analysis that short sprint interval training (SPI) generate greater increase of anaerobic capacity Alactase (AA) than the long sprint interval training (LPI) (MSPI-AA =18.92 MLPI-AA = 18:16) (p .05). Whilst, the long sprint interval training (LPI) generate greater increase of anaerobic capacity Lactase (LA) rather than a short sprint interval training (SPI) (MLPI-LA = 76.16 MSPI-LA = 65.56) (p .05).